2011
DOI: 10.1002/lary.21895
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life indicators according to voice disorders and voice-related conditions

Abstract: Voice disorders stem from a variety of risk factors and biological mechanisms. Such disorders may lead to poor physical and psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 27 publications
3
40
0
Order By: Relevance
“…Respiratory condition is also associated with voice disorder risk . Asthma patients experience voice disorders more frequently than healthy subjects, possibly due to vocal cord trauma caused by chronic coughing, which can result in laryngeal disease .…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory condition is also associated with voice disorder risk . Asthma patients experience voice disorders more frequently than healthy subjects, possibly due to vocal cord trauma caused by chronic coughing, which can result in laryngeal disease .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with asthma, for example, may experience physical limitations because of shortness of breath, but they may also experience vocal fold paralysis as a result of corticosteroids used to treat their disease. 11,18 Individuals with significant occupational voice demands, such as teachers, are at the greatest risk of developing voice problems. 12 Sapir et al 20 reported that more than 30% of teachers quit their jobs because of voice problems, and Smith et al 21 reported that more than 38% of teachers have trouble with teaching because of voice problems and that female teachers tend to have more voice problems than male teachers.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most previous epidemiologic studies of voice disorders have merely focused on voice symptoms. 3,[8][9][10][11][12][13] This study is the first large-scale epidemiologic investigation specifically aimed at characterizing the prevalence of and sociodemographic factors related to voice disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A human communication research effort centered on UVFP would be both patient‐focused and provider‐receptive because some expertly treated patients will still fail to meet vocal production goals . Dysphonia arising from UVFP compromises communicative function and lowers quality of life . Developing innovative behavioral, psychometric, and neuroimaging evaluation tools would help to advance patient care.…”
Section: Introductionmentioning
confidence: 99%